The predictive and prognostic role of metabolic and volume-based parameters of positron emission tomography/computed tomography as non-invasive dynamic biological markers in early breast cancer treated with preoperative systemic therapy - Inno, Alessandro; Peri, Marta; Turazza, Monica; Bogina, Giuseppe; Modena, Alessandra; Massocco, Alberto; Pezzella, Modestino; Valerio, Matteo; Mazzola, Rosario; Olivari, Laura; Severi, Fabrizia; Foti, Giovanni; et al. (Frontiers in Oncology, 2023)
The role of fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) in early breast cancer treated with preoperative systemic therapy (PST) is not yet established in clinical practice. PET parameters have aroused great interest in the recent years, as non-invasive dynamic biological markers for predicting response to PST. In this retrospective study, we included 141 patients with stage II-III breast cancer who underwent surgery after PST. Using ROC analysis, we set optimal cutoff of FDG-PET/CT parameters predictive for pathological complete response (pCR). We investigated the correlation between FDG-PET/CT parameters and pCR, median disease-free survival (DFS), and median overall survival (mOS). At multivariable analysis, baseline SUVmax (high vs low: OR 9.00, CI 1.85 – 61.9, p=0.012) and Delta SUVmax (high vs low: OR 9.64, CI 1.84, 69.2, p=0.012) were significantly associated with pCR rates. Interestingly, we found that a combined analysis of the metabolic parameter Delta SUVmax with the volume-based parameter Delta MTV, may help to identify patients with pCR, especially in the subgroup of hormone receptor positive breast cancer. Delta SUVmax was also an independent predictive marker for both mDFS (high vs low: HR 0.17, 95%CI 0.05-0.58, p=0.004) and mOS (high vs. low: HR 0.19, 95%CI 0.04-0.95, p=0.029). Our results suggest that Delta SUVmax may predict survival of early BC patients treated with PST.